2020
DOI: 10.1088/1755-1315/588/5/052018
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven parametric tool for under-specified LCA in the design phase

Abstract: Life Cycle Assessment (LCA) is increasingly applied to evaluate the environmental performance of buildings. However, current tools for building LCA require detailed information not available in the decisive early design stages. As a result, LCA is usually applied as post-design evaluation and not used to improve the building design. The goal of this paper is to adapt the method of structured under-specified LCA to the Swiss context and implement it in a design-integrated tool. The users of the tool should be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…Recent literature review of LCA in design revealed that most LCAs are reactive (after design completion), but that proactive methods have better potential to effect actual change, a factor acknowledged by those innovating in LCA capabilities for early design [34][35][36]. Of the literature that incorporates LCA at multiple points throughout design (table 1-'Throughout'), most are unclear about how the LCA influences the design and are presented more as tracking mechanisms used at discrete points in the process rather than as a continuously evolving, iterative analysis, as part of an IDP that informs all disciplines [28][29][30][31][32][33].…”
Section: Lca In the Design Processmentioning
confidence: 99%
“…Recent literature review of LCA in design revealed that most LCAs are reactive (after design completion), but that proactive methods have better potential to effect actual change, a factor acknowledged by those innovating in LCA capabilities for early design [34][35][36]. Of the literature that incorporates LCA at multiple points throughout design (table 1-'Throughout'), most are unclear about how the LCA influences the design and are presented more as tracking mechanisms used at discrete points in the process rather than as a continuously evolving, iterative analysis, as part of an IDP that informs all disciplines [28][29][30][31][32][33].…”
Section: Lca In the Design Processmentioning
confidence: 99%
“…Environmental concerns are seldom accommodated in such thinking [48]. Although methodologies and procedures for quantifying the environmental impact of structures are by now available, mostly related to LCA, these are far from a broad and efficient implementation in daily structural design procedures [81]. The baseline scenario represents this description of ''Current practice''.…”
Section: Scenariosmentioning
confidence: 99%
“…The moderate action scenario assumes that the current German climate protection plan to move towards a carbon-neutral society [81] will translate into coordinated, although ''moderate measures'', affecting the structural engineering sector. Given the strong evidence of the environmental benefit of timber as primary structural material 2.…”
Section: • Moderate Action (Ma)mentioning
confidence: 99%
“…These parameters are those that are identified to be of high importance to the inventories, as shown in Figure 1. Parameterization allows multiple variants of a base inventory model to be generated by varying key parameters or levers, which are usually external to the unit processes [64][65][66][67]. By doing so, we can assess the effect of parameter variation on the overall footprints of the value chains investigated.…”
Section: Model Descriptionmentioning
confidence: 99%